Impact of body mass index on overall survival in patients with metastatic breast cancer - Saleh, Khalil (Breast, 2020)
BACKGROUND: High Body mass index (BMI) is a risk factor for breast cancer among postmenopausal women and an adverse prognostic factor in early-stage. Little is known about its impact on clinical outcomes in patients with metastatic breast cancer (MBC). METHODS: The National ESME-MBC observational cohort includes all consecutive patients newly diagnosed with MBC between Jan 2008 and Dec 2016 in the 18 French comprehensive cancer centers. RESULTS: Of 22 463 patients in ESME-MBC, 12 999 women had BMI data available at MBC diagnosis. Median BMI was 24.9 kg/m(2) (range 12.1–66.5); 20% of women were obese and 5% underweight. Obesity was associated with more de novo MBC, while underweight patients had more aggressive cancer features. Median overall survival (OS) of the BMI cohort was 47.4 months (95% CI [46.2–48.5]) (median follow-up: 48.6 months). Underweight was independently associated with a worse OS (median OS 33 months; HR 1.14, 95%CI, 1.02–1.27) and first line progression-free survival (HR, 1.11; 95%CI, 1.01; 1.22), while overweight or obesity had no effect. CONCLUSION: Overweight and obesity are not associated with poorer outcomes in women with metastatic disease, while underweight appears as an independent adverse prognostic factor.